2015
DOI: 10.1186/s13100-015-0053-5
|View full text |Cite|
|
Sign up to set email alerts
|

Ribosomal protein and biogenesis factors affect multiple steps during movement of the Saccharomyces cerevisiae Ty1 retrotransposon

Abstract: BackgroundA large number of Saccharomyces cerevisiae cellular factors modulate the movement of the retrovirus-like transposon Ty1. Surprisingly, a significant number of chromosomal genes required for Ty1 transposition encode components of the translational machinery, including ribosomal proteins, ribosomal biogenesis factors, protein trafficking proteins and protein or RNA modification enzymes.ResultsTo assess the mechanistic connection between Ty1 mobility and the translation machinery, we have determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 73 publications
(107 reference statements)
0
20
1
Order By: Relevance
“… Suresh et al (2015) reported that Ty1i RNA and p22/p18 levels increase in several ribosome biogenesis mutants including rps0b Δ. Therefore, endogenous levels of Ty1 mRNA, Ty1i RNA, Gag, and p22/p18 were determined in loc1 Δ, rps0b Δ, and rpl7a Δ CNC mutants ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“… Suresh et al (2015) reported that Ty1i RNA and p22/p18 levels increase in several ribosome biogenesis mutants including rps0b Δ. Therefore, endogenous levels of Ty1 mRNA, Ty1i RNA, Gag, and p22/p18 were determined in loc1 Δ, rps0b Δ, and rpl7a Δ CNC mutants ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, endogenous levels of Ty1 mRNA, Ty1i RNA, Gag, and p22/p18 were determined in loc1 Δ, rps0b Δ, and rpl7a Δ CNC mutants ( Figure 4 ). To clearly distinguish Ty1i RNA from Ty1 mRNA ( Saha et al 2015 ; Suresh et al 2015 ), poly(A) + RNA was subjected to northern blot analysis using a 32 P-labeled riboprobe containing Ty1 nucleotides 1266–1601 that hybridizes with Ty1 mRNA and Ty1i transcripts; ACT1 mRNA served as a loading control ( Figure 4A ). Ty1 transcripts were below the limit of detection in wild type or CNC − mutants since there is only one Ty1 element present in the CNC − background.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A key insight into the mechanism by which tail module triad gene deletions cause decreased Ty1 mobility was obtained by northern analysis of Ty1 polyA + transcripts, which revealed increased levels of the internally generated, inhibitory Ty1i transcript in these deletion mutants (Fig 4). Increased Ty1i RNA was accompanied by elevated levels of p22-Gag, which interferes with VLP formation and production of Ty1 cDNA [25,30]. The increased expression of Ty1i is caused by a direct effect on transcription, as opposed to Ty1i RNA processing or stability, based on the altered occupancy of Pol II in a med3 Δ med15 Δ yeast mutant (Fig 4).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the original version of this article [ 1 ] contained an error. The author’s name, ‘Arun Kananganat’ , was spelt incorrectly.…”
Section: Erratummentioning
confidence: 99%